“WHAT IS THE URGENCY?”: YOUTUBE PUBLIC RESPONSE ON FEMICIDE AWARENESS IN INDONESIA (Proceedings of the International Conference on Future of Women, 2025)
Femicide refers to the killing of women due to their gender. The Indonesian NationalCommission on Violence Against Women (Komnas Perempuan) reported hundreds of femicidecases annually in Indonesia from 2021 to 2023. However, the term remains largely unfamiliar withinthe country, despite being one of the most extreme and brutal forms of violence against women.Raising public awareness of femicide is crucial and can be achieved through educational efforts,including coverage of femicide cases and explanations of the concept. In the digital era, YouTubehas emerged as a potential platform for such education. As the third most frequently used socialmedia platform in Indonesia, YouTube has become a primary source of news for many Indonesians.This study aims to describe femicide-related content uploaded to YouTube and to analyzeIndonesian netizens’ responses to the issue. Using data collected via the YouTube API (ApplicationProgramming Interface), the study identified 29 femicide-related videos in the Indonesian languageand analyzed 81% comments of all. Using qualitative content analysis for social media, the studyrevealed two main categories which are Femicide Issue and Netizens’ View. Femicide Issue consistof two themes, named causes and prevention that reflect Indonesian patriarchy and religious culture.Meanwhile the category of Netizens’ View holds two other themes, judgement and reflection, showsthat Indonesians still see femicide as an unimportant issue even though they feel bad about it. Thestudy emphasizes the need for comprehensive strategies and collaboration among variousstakeholders to bring this critical issue to Indonesian public attention.
Keywords: femicide; YouTube comment; Indonesia; public awareness; qualitative content analysis Introduction